IMPLEMENTASI KEBIJAKAN PENINGKATAN PELAYANAN KESEHATAN (Tentang Pelaksanaan Program Jaminan Mutu Pelayanan Kesehatan Dasar Di Puskesmas Ngronggot Kabupaten Nganjuk) - YENIK PUJOWATI (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
Implementation of Quality Assurance and the Public Health Service especially basic health care is a must. Quality assurance is not only a humanitarian obligation, ethical, administrative solely, but it has been a legal obligation as what has been stipulated in Law no. 23 of 1992 on Health in the Ministry of Health Decree No. 125/Menkes/SK/II/2008. This study examines how to increase health care policy implementation in Ngronggot health center, Nganjuk . This study concluded that actors involved in the implementation of cross-cutting health services to perform its role in different way. Efforts to increase public awareness in order to create a healthy living behaviors are difficult to achieve, because it is not supported by socio-economic factors, which is still low. Contributing factor in the implementation of this policy is the availability of regulation as law. while the inhibiting factor is the lack of resources in policy implementation.